Smart study table / Nur Ikma Adila Edi Armiza ... [et al.] - Edi Armiza, Nur Ikma Adila; Amirudin, Anastasia Tania; Abd Farouk, Nur Aqilah; Mohd Noordin, Nur A’isya Syaahirah; Zali, Siti Nur Aqilah (2023)
The Smart Study Table represents a groundbreaking venture in the realm of educational technology, addressing the evolving needs of students in the contemporary learning environment. In response to the increasing integration of technology in education, our product is designed to seamlessly blend traditional study spaces with cutting-edge features. This innovative study table incorporates Internet of Things (IoT) connectivity, offering students a dynamic and interactive learning experience. The table's adjustable ergonomic design ensures optimal comfort, recognizing the importance of a conducive physical environment for effective studying. By integrating touch controls, it provides an intuitive interface for users to interact with various devices and applications. The core objective of the Smart Study Table is to enhance productivity and efficiency in learning. With a keen focus on adaptability, the table accommodates diverse study preferences and work styles. It serves as a hub for digital devices, promoting a clutter-free and organized workspace conducive to concentration and focus. Recognizing the growing demand for sustainable solutions, the Smart Study Table is crafted with environmentally friendly materials and energy-efficient components. This not only aligns with contemporary environmental concerns but also positions our product as a responsible and forward-thinking choice in the market. In terms of market positioning, the Smart Study Table targets the rising demand for technologically advanced educational tools. With its integration of smart features, it caters to the tech-savvy generation of students seeking innovative solutions for their academic pursuits.